Status of clinical research in neurology in Germany—A national survey - Lohmann, Lisa; Lammerskitten, Anna; Korsen, Melanie; Dodel, Richard; Gaul, Charly; Hamer, Hajo; Kleineberg, Nina N.; Ludolph, Albert C.; Mayer, Geert; Poli, Sven; Saur, Dorothee; Steinhoff, Bernhard J.; et al. (European Journal of Neurology, 2021)
Background and purpose: To provide an overview on the status of clinical research in neurology in Germany. Methods: German university hospitals, nonuniversity hospitals, and neurological medical practices were surveyed regarding their clinical research activities during the period 2013 to 2017. Results: Fifty percent of university hospitals, 10.6% of nonuniversity hospitals, and 5.2% of medical practices in Germany responded to our questionnaire. More than 80% of the clinical studies conducted have been phase III/IV and noninterventional trials (NISs), whereas <1% have been phase I and 3.5% investigator-initiated trials (IITs). University hospitals have conducted most of the phase II–IV trials. NISs have been predominantly performed by medical practices. Fifty-six percent of the university hospitals and less of the nonuniversity institutions confirmed the implementation of standard operating procedures (SOPs). In university hospitals, on average, 11 physicians had acquired a good clinical practice certificate. Overall, 43% of all trials have been performed in neuroimmunology. Conclusions: The status of clinical research in neurology in Germany is predominated by NISs and late-phase trials, potentially due to a general lack of easily accessible funding, which leads to a highly competitive environment and fewer opportunities to perform early-phase clinical trials as well as IITs. Our results indicate that there is substantial need for structured support for creating and implementing SOPs to maintain quality standards and guarantee uniformity of performance. This survey assessed many aspects of clinical research and serves as guidance for providing ideas for structured improvement of clinical research in neurology in Germany.
CRIS-Team Scopus Importer:2021-03-19
Keywords: clinical research; Germany; good clinical practice; survey